Capabilities of intraoperative photodynamic therapy for treatment of locally advanced breast cancer - E. V. Filonenko; E. K. Saribekyan; V. I. Ivanova-Radkevich (Biomedical Photonics)
The original method of intraoperative photodynamic therapy for multimodality treatment of primary and recurrent breast cancer for devitalization of malifnant cells at wound surface and for prevention of further cancer dissemination was developed in P.A. Herzen Moscow Cancer Research Institute. The developed method was approved in 79 patients with locally advanced breast cancer stage IIB and IIIA,B,C with poor prognostic factors. For photodynamic therapy the photosensitizer photosens (30 min intravenous infusion at dose of 0.3 mg/kg of body weight 2 h before surgery) was used in 56 patients; alasens (solution in 100 ml of still drinking water, orally at dose of 30 mg/kg of body weight 2 h before general anesthesia) — in 23 patients. The surgical field was irradiated on a single occasion: the dose of laser irradiation on the bed of removed primary or recurrent tumor was 20–30 J/cm2, in the removed regional lymph nodes area – 50 J/cm2. Long-term results of the treatment were assessed in 34 patients: there were no disease progression in 50% of patients, 14.7% of patients had locoregional recurrence, distant metastases were in 35.3% of patients. The level of photosensitizer accumulation in tissue was additionally analyzed in 26 patients by fluorescence intensity in tumor and in normal breast tissue. After injection of alasens the increase in level of alasens-induced protoporphyrin IX fluorescence was recorded in tumor (the average diagnostic parameter was 6.5 a.u.) and in intact breast tissue (an average of 0.47 a.u.), tumor/normal tissue fluorescence contrast varied from 3 to 33. The level of protoporphyrin IX accumulation was noticed to be lower in tumors with pathomorphological response after neoadjuvant therapy. For photosens value of the average diagnostic parameter in normal breast tissue was 5.6 a.u., in tumor – 34.3 a.u., tumor/normal tissue fluorescence contrast – from 2 to 9.